Determinants of survival in sinonasal and skull base chondrosarcoma: An analysis of the National Cancer Database. Issue 5 (26th October 2021) - Rimmer, Ryan A.; Mace, Jess C.; Andersen, Peter E.; Cetas, Justin S.; Ciporen, Jeremy N.; Dogan, Aclan; Smith, Timothy L.; Geltzeiler, Mathew
Abstract: Background: Chondrosarcomas are rare, malignant chondroid tumors that can occur in the sinonasal and skull base regions. Surgery is a mainstay of treatment, but complete resection can be challenging because of the close proximity of critical neurovascular structures. Because of their rarity and relatively indolent nature, optimal treatment regimens are not established. Our objective was to assess determinants of survival for sinonasal and skull base chondrosarcomas utilizing the National Cancer Database (NCDB). Methods: The NCDB (2004–2017) was queried for cases of sinonasal and skull base chondrosarcoma. Multivariate hazard regression modeling was used to identify significant predictors of 60‐month and 120‐month overall survival (OS). Results: Seven hundred thirty‐six cases met inclusion criteria. OS for all treatment types was 84.7% [SE±0.02] at 60 months and 75.6% [SE±0.02] at 120 months. Surgery with or without adjuvant treatment was found to associate with highest OS at 60 and 120 months. For patients receiving adjuvant radiation during treatment, proton therapy had significantly better OS at 60 months (95.4% [SE±0.03] vs 82.3% [SE±0.03], ‐ 2 = 5.27; p = 0.02) and 120 months (85.1% [SE±0.08] vs 72.8% [SE±0.05], ‐ 2 = 4.11; p = 0.04) compared with conventional external beam. After adjustment for primary site, multivariate Cox regression modeling (n = 561) identified cofactors significantly associated with variation in mortality risk at 60 and 120 months, including age, Charlson‐Deyo total score ≥ 3, insurance provision status, and tumor grade. Conclusions: Sinonasal and skull base chondrosarcoma are primarily treated with surgery with favorable OS. Adjuvant treatment may be required and proton radiation was associated with improved 60‐month and 120‐month survival compared with conventional radiation.